2022
DOI: 10.1021/acs.orglett.2c01409
|View full text |Cite
|
Sign up to set email alerts
|

Accessing Illusive E Isomers of α-Ester Hydrazones via Visible-Light-Induced Pd-Catalyzed Heck-Type Alkylation

Abstract: A visible-light-induced Pd-catalyzed stereoselective synthesis of alkylated ester hydrazones has been developed. This method operates via generation of a nucleophilic carbon-centered radical from alkyl bromide, iodide, or redox-active ester, followed by its addition to hydrazone, and a subsequent desaturation by palladium. The majority of products have E configuration, which are inaccessible by conventional condensation methods. In addition, a sequential C,N-alkylation protocol has been developed: a reaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…We commenced our studies with examining a model reaction between gem -difluorocyclopropene 1a and styrene 2a under standard visible light/Pd conditions (Table ). Consistently with our previous studies, , the combination of Pd­(OAc) 2 and bidentate Xantphos proved to be the most efficient catalytic system. An extensive evaluation of monodentate additive ligand ,, indicated P­(2-Furyl) 3 as a superior ligand.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…We commenced our studies with examining a model reaction between gem -difluorocyclopropene 1a and styrene 2a under standard visible light/Pd conditions (Table ). Consistently with our previous studies, , the combination of Pd­(OAc) 2 and bidentate Xantphos proved to be the most efficient catalytic system. An extensive evaluation of monodentate additive ligand ,, indicated P­(2-Furyl) 3 as a superior ligand.…”
Section: Resultssupporting
confidence: 91%
“…Evidently, we recognized the need for additives to promote the in situ generation of PdH species. Therefore, in contrast to the previously developed basic conditions for photoinduced Heck reactions, ,, we introduced an acidic environment, where acetic acid was identified as the key beneficial hydrogen donor, operating with dimethylphenylsilane as a hydride codonor. It was also found that employment of tetrabutylammonium bromide (TBAB), an exogenous halide counterion source, was crucial for further improvement of the reaction efficiency .…”
Section: Resultsmentioning
confidence: 99%
“…Further elaboration of the Pd(0/II/I) manifold to include the alkyl-Heck-type coupling between alkyl radicals and Ncontaining olefins resulted in the synthesis of pyridazines 46 in one pot (Scheme 13). 41 The mechanism of the reaction starts with the SET between photoexcited palladium complex and alkyl halide or redox active ester to produce nucleophilic hybrid alkyl palladium radical A, capable of radical addition to hydrazone 44 producing the nitrogencentered radical B. The latter, either upon direct oxidation or recombination (C) followed by -hydride elimination, could yield alkylated diazene D, which under basic condi-tions is tautomerized to hydrazone E. Importantly, this product can be isolated exclusively as the E-isomer, which is highly challenging to access by other methods.…”
Section: Light-induced Radical Heterocyclizationmentioning
confidence: 99%
“…In cross-coupling reactions, considerations related to oxidative addition and the stability of the alkyl palladium species result in a scenario where sp 2 halides (CX) are significantly more prevalent than their alkyl counterparts. , Another challenge with alkyl-palladium species is the undesired β-hydride elimination. The advent of excited-state Pd-catalysis pioneered by Gevorgyan and Fu , overcomes this limitation by designing a system that proceeds via single electron transfer from a hybrid Pd/radical species. The Rueping group has recently applied excited-state Pd-catalysis for synthesizing oxindoles and alkylated amines .…”
Section: Introductionmentioning
confidence: 99%